2018
DOI: 10.1002/star.201700198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid Methanol Treatment and Heat Moisture Treatment on In Vitro Digestibility and Estimated Glycemic Index of Raw and Gelatinized Sago (Metroxylon Sagu) Starch

Abstract: This study aims to elucidate the effect of dual modification of acid methanol treatment (AMT) and heat moisture treatment (HMT) on digestibility and glycemic index (eGI) of sago starch in the raw and gelatinized state. AMT is conducted (1 and 2 mL of hydrochloric acid) prior to HMT (15 and 20% moisture content). Thermal behavior, pasting properties, morphology, and relative crystallinity of raw starches are investigated. Dual modification is found to significantly increase the resistant starch (RS) content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This was due to the disruption of starch molecules by acid. The acid molecules could break some of the starch molecules’ glycosidic bonds causing the molecules to decrease in size during gelatinization thereby inhibiting retrogradation since these smaller molecules cannot readily reassociate, which makes it difficult for retrogradation to occur . Shi and Seib reported that starch retrogradation was not favored by chains that were too short or too long, with the optimum size range being between about 14 and 24.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the disruption of starch molecules by acid. The acid molecules could break some of the starch molecules’ glycosidic bonds causing the molecules to decrease in size during gelatinization thereby inhibiting retrogradation since these smaller molecules cannot readily reassociate, which makes it difficult for retrogradation to occur . Shi and Seib reported that starch retrogradation was not favored by chains that were too short or too long, with the optimum size range being between about 14 and 24.…”
Section: Resultsmentioning
confidence: 99%
“…The acid molecules could break some of the starch molecules' glycosidic bonds causing the molecules to decrease in size [27] during gelatinization thereby inhibiting retrogradation since these smaller molecules cannot readily reassociate, which makes it difficult for retrogradation to occur. [28] Shi and Seib [29] reported that starch retrogradation was not favored by chains that were too short or too long, with the optimum size range being between about 14 and 24. This result could explain the harder texture noted in the repeatedly freezethaw untreated cooked rice, suggesting that repeated freeze-thaw cycles lead to increased retrogradation of starch granules whereas acid treatment can reduce starch retrogradation producing freeze-thawed acid-treated cooked aged rice with a softer texture than untreated rice.…”
Section: Retrogradation Properties Of Unfrozen and Freeze-thawed Cookmentioning
confidence: 99%
“…An amount of 3.0 g of starch (dry basis) was adjusted with distilled water to achieve constant weight of 28.0 g in the aluminum canister. The heating and cooling profile used was according to Ng et al [54]. The temperature was first held at 50 • C for 1 min and raised to 95 • C (12 • C/min) and held for another 2.5 min before cooling down to 50 • C (12 • C/min).…”
Section: Pasting Propertiesmentioning
confidence: 99%
“…Therefore, some efforts have to be made to increase sago starch's utilization in the food industries, through physical and chemical modification. Moreover, sago starch has to change its status from a staple food to an income generating source [3], particularly in eastern part of Indonesia.…”
Section: Introductionmentioning
confidence: 99%